Quantifying the Precipitation Loss of Radiation Belt Electrons During a Rapid Dropout Event. Issue 10 (19th October 2017) - Pham, K. H.; Tu, W.; Xiang, Z.
Abstract: Relativistic electron flux in the radiation belt can drop by orders of magnitude within the timespan of hours. In this study, we used the drift‐diffusion model that includes azimuthal drift and pitch angle diffusion of electrons to simulate low‐altitude electron distribution observed by POES/MetOp satellites for rapid radiation belt electron dropout event occurring on 1 May 2013. The event shows fast dropout of MeV energy electrons at L  > 4 over a few hours, observed by the Van Allen Probes mission. By simulating the electron distributions observed by multiple POES satellites, we resolve the precipitation loss with both high spatial and temporal resolutions and a range of energies. We estimate the pitch angle diffusion coefficients as a function of energy, pitch angle, and L ‐shell and calculate corresponding electron lifetimes during the event. The simulation results show fast electron precipitation loss at L  > 4 during the electron dropout, with estimated electron lifetimes on the order of half an hour for MeV energies. The electron loss rate shows strong energy dependence with faster loss at higher energies, which suggest that this dropout event is dominated by quick and localized scattering process that prefers higher energy electrons. The improved temporal and spatial resolutions of electron precipitation rates provided by multiple low‐altitude observations can resolve fast‐varying electron loss during rapid electron dropouts (over a few hours), which occur too fast for a single low‐altitude satellite. The capability of estimating the fast‐varying electron lifetimes during rapid dropout events is an important step in improving radiation belt model accuracy. Key Points: Multiple low‐altitude satellites can simulate rapid dropouts that single satellites cannot Capable of simulating pitch angle diffusion coefficient with magnetic local time dependence Provides an estimate for precipitation loss rate and electron lifetimes